NEEDED: MORE INFORMATIVE AND UNDERSTANDABLE FINANCIAL STATEMENTS FROM GOVERNMENTAL UNITS. - Hylton, Delmer P. (The Accounting Review, 1957)
Abstract Accounting in governmental units and particularly in municipalities, has improved during the last two or three decades. During this period, the accrual basis has become accepted procedure for handling most items of revenue and expenditure. In one important respect, progress seems to be lacking in the field of governmental accounting. The published reports of governmental units show little, if any, progress over those which were published earlier. If publishing a report of some sort can be assumed to be better than no report at all, then progress has been made. The typical report of a municipality is a lengthy, detailed, footnoted conglomeration of prose and figures. Page after page of tables, financial statements, charts and other data is the rule. Few accountants can thaw basic conclusions from these statements without intense study. For purposes of financial control, it is necessary to keep separate records for each fund and reports showing the status of each fund are required. But whether these individual reports are the ones which should be generally distributed is another and different question.